Integration of stakeholders in the innovation process of transportation networks - Maximilian Leven; Wolfgang Kersten (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Transportation networks play an important role in providing reliable and resilient transport solution for their customers. To stay competitive, members of freight forwarding networks use their joint knowledge to innovate. This paper provides information about the influence of commitment on the success factor of integration of stakeholders. Methodology: To evaluate the influence an online survey was conducted with participants of several transportation networks. The findings of the quantitative study were analysed with the help of the partial least square (PLS) approach. Findings: The study demonstrates that the attitude-oriented commitment has a positive effect on the integration of stakeholders. Hence the proposed hypothesis of a positive effect was confirmed. Originality: The presented study provides a guideline for members of transportation networks to precisely ensure that the success factor integration of stakeholders is considered in the innovations process. Furthermore with regard to the success factor the influence of attitude-oriented commitment needs to be involved to enhance the output within the inovation process.
urn:nbn:de:gbv:830-882.0161870; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation management; technology management